An Introductory Course of Quantitative Chemical Analysis : With Explanatory Notes - Talbot, Henry Paul, 1864-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"An Introductory Course of Quantitative Chemical Analysis" by Henry Paul Talbot is a scientific publication aimed at students of chemistry, reflecting practices likely developed in the early 20th century. The text serves as a comprehensive guide to quantitative analysis, emphasizing detailed procedural instructions intended for beginners who have completed qualitative analysis. The opening of the manual provides insight into its structure and goals, primarily focusing on establishing a solid foundation for students venturing into quantitative analysis. Talbot explains the distinctions between various analytical methods$1 (Bgravimetric, volumetric, and colorimetric$1 (Band underscores the significance of careful attention to detail in laboratory practices. The introduction also emphasizes the importance of pedagogical clarity, recommending that students engage with both the instructional material and hands-on practice to enhance their understanding of analytical techniques. It sets the stage for subsequent chapters, which will delve deeper into specific methods and protocols for conducting analyses, utilizing equipment, and understanding the principles underlying quantitative measurements. (This is an automatically generated summary.)s
Release date is 2004-06-30
Produced by Kevin Handy, Dave Maddock, Josephine Paolucci and the Online Distributed Proofreading Team
Keywords: Chemistry, Analytic -- Quantitative